Improvement of HbA1c in Patients with Type 2 Diabetes Mellitus and Rheumatoid Arthritis Treated with bDMARDs - Lurati A (Dove Medical Press, 2021)
Alfredomaria Lurati,1 Antonella Laria,1 Daniela Mazzocchi,1 Katia Angela Re,1 Maria Grazia Marrazza,1 Paola Maria Faggioli,2 Antonino Mazzone2 1Rheumatology Unit, Fornaroli Hospital Magenta Italy, Milan, Italy; 2Internal Medicine Unit, Legnano Hospital, Milan, ItalyCorrespondence: Alfredomaria LuratiRheumatology Unit Fornaroli Hospital Magenta Italy, Via Donatore Sangue 50, Milan, 22100, ItalyEmail alfredomaria.lurati@asst-ovestmi.itObjective: The aim of our study was to evaluate the possible role of biological treatments for rheumatoid arthritis (RA) in improving the glycemic profile in patients affected not only by RA but also by type 2 diabetes mellitus (2TDM).Methods: An observational retrospective study was conducted using data from patients referred to our Rheumatology Unit. Patients with active RA despite standard DMARDs therapy and concomitant 2TDM were selected into one of five exposure groups to first-line bDMARDs (adalimumab, golimumab, etanercept, tocilizumab, sarilumab) and observed for the outcome of CRP, ESR, DAS28CRP and glycated hemoglobin (HbA1c) variations.Results: After the start of treatment, there was a significant reduction in the values of acute phase reactants ESR and CRP (p< 0.01), DAS28-CRP (p< 0.01) and HbA1C (p< 0.05), in the absence of any confounding factors such as a reduction in BMI or a change in steroid doses. There was no statistically significant difference between the various treatments. Anti-IL6 drugs appear to be associated with a slightly greater reduction in HbA1c values, bordering on statistical significance (p=0.047).Conclusion: Initiation of a bDMARD appears to be associated with an improvement in concomitant 2TDM in patients with active RA, which, in the first hypothesis, is linked with a reduction of the inflammatory milieu.Keywords: diabetes mellitus, rheumatoid arthritis, bDMARDs